The sum of numerator and denominator of a fraction is greater by 1 than thrice the numerator is decreased by 1 then the fraction reduced to 1/3 find the fraction
Answers
S O L U T I O N :
Let the place of numerator be x & let the place of denominator be y respectively.
- The fraction become = x/y
According to the question :
1st case :
➝ x + y = 3x + 1
➝ x - 3x = 1 - y
➝ -2x = 1 - y............(1)
2nd case :
➝ x - 1/y = 1/3
➝ 3(x - 1) = y(1)
➝ 3x - 3 = y............(2)
∴Putting the value of y in equation (1), we get;
➝ -2x = 1 - (3x - 3)
➝ -2x = 1 - 3x + 3
➝ -2x = -3x + 4
➝ -2x + 3x = 4
➝ x = 4
∴ Putting the value of x in equation (1), we get;
➝ -2(4) = 1 - y
➝ -8 = 1 - y
➝ -8 - 1 = -y
➝ -9 = -y
➝ y = 9
Thus,
- Numerator, (N) = 4
- Denominator, (D) = 9
The fraction will be x/y = 4/9 .
Answer:
Given :-
- The sum of numerator and denominator of a fraction is greater by 1 than thrice the numerator is decreased by 1 then the fraction reduced to 1/3.
To Find :-
- What is the fraction.
Solution :-
Let, the fraction be x/y
According to the question,
➣ The sum of numerator and denominator of a fraction is greater by 1 than thrice the numerator.
⇒ x + y = 3x + 1
⇒ y = 3x - x + 1
⇒ y = 2x + 1 .......... equation no (1)
➣ Denominator is decreased by 1 than the fraction reduced by 1/3.
⇒ x - 1/y = 1/3
⇒ 3(x - 1) = y
⇒ 3x - 3 = y
⇒ 3x - y = 3 ......... equation no (2)
➣ Now, putting the value of x from equation no (1) in equation no (2) we get,
⇒ 3x - y = 3
⇒ 3x - (2x + 1) = 3
⇒ 3x - 2x - 1 = 3
⇒ x = 3 + 1
➠ x = 4
➣ Again, putting the value of x in the equation no (1) we get,
⇒ y = 2x + 1
⇒ y = 2(4) + 1
⇒ y = 8 + 1
➥ y = 9
Hence, the required fraction will be,
↦ x/y
➽ 4/9
∴ The fraction will be 4/9 .